A Look Back: Computers in the classroom, as covered in Kappan. (March 2021) - Preston, Teresa
The potential of computers to transform schools has been a significant concern of educators since at least the 1960s. Teresa Preston explores how Kappan authors covered the computer age, beginning with explorations of computer-assisted instruction in the 1960s and continuing through the development of microcomputers in the 1980s. Although authors had great hopes for how computers could provide more engaging and individualized experiences, they also acknowledged that implementing technology would not be easy and that changes might be more gradual than technology advocates hoped .